Changes in chemical properties of organic matter with intensified rice cropping in tropical lowland soil - Olk, D.C.; Cassman, K.G.; Randall, E.W.; KINCHESH, P.; SANGER, L.J.; ANDERSON, J.M. (Wiley, 1996)
Rice systems in Asia have intensified rapidly in the past 30 years, and significant areas of irrigated lowland rice are now supporting two or three rice crops per year. Our objective was to compare the chemical composition of soil organic matter (SOM) from four fields with different histories of rice cropping intensity and soil submergence: (i) a single‐crop rainfed, dryland rice system without soil submergence, (ii) an irrigated rice and soybean rotation, and irrigated (iii) double‐ or (iv) triple‐crop rice systems in which soil remains submerged during much of the year. In all four soils, extracted mobile humic acid (MHA) and calcium humate (CaHA) fractions were of modern age by 14C‐dating, and represented about 20% of total N and organic C. The MHA was enriched in N and hydrolysable amino acids (AA) compared with CaHA in all soils. With increased frequency of irrigated rice cropping, however, there was a large increase in phenolic content of SOM. We speculate that slower lignin decomposition caused by deficiency of O2 in submerged soil leads to incorporation of phenolic moieties into young SOM fractions. The increased phenolic character of these fractions may influence N cycling and the N supplying capacity of lowland soils supporting two or three annual crops of irrigated rice.